Analisis Kewenangan Presiden dalam Pembentukan Peraturan Pemerintah Pengganti Undang-Undang (PERPPU) Berdasarkan Perspektif Konstitusi dan Teori Perundang-Undangan: Studi Kasus UU No. 6 Tahun 2023 tentang Penetapan PERPPU No. 2 Tahun 2022 - Chadijah, Siti; Hadi, Abdul (Journal of Contemporary Law Studies, 2024)
This study examines the President's authority to issue Government Regulations in Lieu of Laws (PERPPU) based on constitutional perspectives and statutory theory, particularly in light of Law No. 6 of 2023 regarding the stipulation of PERPPU No. 2 of 2022. According to Article 22 of the 1945 Constitution of the Republic of Indonesia, the President may enact PERPPU "in urgent matters." However, this provision has led to legal uncertainty and contradicts the Constitution's requirement for objective circumstances of compelling urgency. This research aims to describe and analyze the formation of PERPPU, exploring the constitutional basis and legislative theory underpinning this process. Using normative legal research methods, the study reviews library materials and secondary data, focusing on relevant regulations. Normative legal research considers law as a set of norms or rules guiding societal behavior, and thus, this study emphasizes the inventory of positive law, legal principles, doctrines, concrete case discoveries, legal systematics, law synchronization levels, comparative law, and legal history. The findings indicate significant issues in the current practice of PERPPU formation, raising questions about the balance between executive power and legal certainty. The study concludes that a clearer framework and stricter criteria are necessary to align the practice with constitutional mandates and ensure fair legal processes.